Iron overloaded polarizes macrophage to proinflammation phenotype through ROS/acetyl‐p53 pathway - Zhou, Yun (Cancer Med, 2018)
PURPOSE: Macrophages play critical roles in inflammation and wound healing and can be divided into two subtypes: classically activated (M1) and alternatively activated (M2) macrophages. Macrophages also play important roles in regulating iron homeostasis, and intracellular iron accumulation induces M1‐type macrophage polarization which provides a potential approach to tumor immunotherapy through M2 tumor‐associated macrophage repolarization. However, the mechanisms underlying iron‐induced M1 polarization remain unclear. METHODS: Western blotting, qRT‐PCR, and flow cytometry were used to detect the polarization indexes in RAW 264.7 murine macrophages treated with iron, and Western bloting and qRT‐PCR were used to detect p21 expression. The compound 2,7‐dichlorofluorescein diacetate was used to measure reactive oxygen species (ROS) levels in macrophages after iron or N‐acetyl‐l‐cysteine (NAC) treatment. The p300/CREB‐binding protein (CBP) inhibitor C646 was used to inhibit p53 acetylation, and Western bloting, qRT‐PCR, and immunofluorescence were used to detect p53 expression and acetylation. BALB/c mice were subcutaneously injected with H22 hepatoma cells, and macrophage polarization status was investigated after tail intravenous injection of iron. Immunohistochemical staining was used to evaluate the protein expression of cluster of differentiation 86 (CD86) and EGF‐like module‐containing mucin‐like hormone receptor‐like 1 (F4/80) in the subcutaneous tumors. RESULTS: Iron overload induced M1 polarization by increasing ROS production and inducing p53 acetylation in RAW cells, and reduction in ROS levels by NAC repressed M1 polarization and p53 acetylation. Inhibition of acetyl‐p53 by a p300/CBP inhibitor prevented M1 polarization and inhibited p21 expression. These results showed that high ROS levels induced by iron overload polarized macrophages to the M1 subtype by enhancing p300/CBP acetyltransferase activity and promoting p53 acetylation.